2021
DOI: 10.1097/meg.0000000000002215
|View full text |Cite
|
Sign up to set email alerts
|

Association between aspartate aminotransferase-to-alanine aminotransferase ratio and insulin resistance among US adults

Abstract: Objective To determine whether a low aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AST/ ALT ratio) is associated with insulin resistance among those without liver dysfunction. Methods In this cross-sectional study of the National Health and Nutrition Examination Survey (NHANES) 2011-2016, we included 2747 (1434 male and 1313 nonpregnant female) adults ≥20 years without evidence of liver dysfunction (ALT<30 in male and <19 in female, negative viral serologies, no excess alcohol consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In the Korean population, a high ALT/AST ratio determined insulin resistance and obesity in adults ( 14 ). Similarly, surveys based on American populations revealed an increased risk of insulin resistance with lower AST/ALT ratio ( 32 ). Since insulin resistance is an important characteristic of diabetes, several recent studies based on Japanese populations also further elucidated a conclusion that there was also a correlation between low AST/ALT ratio and the incidence of diabetes ( 15 , 16 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Korean population, a high ALT/AST ratio determined insulin resistance and obesity in adults ( 14 ). Similarly, surveys based on American populations revealed an increased risk of insulin resistance with lower AST/ALT ratio ( 32 ). Since insulin resistance is an important characteristic of diabetes, several recent studies based on Japanese populations also further elucidated a conclusion that there was also a correlation between low AST/ALT ratio and the incidence of diabetes ( 15 , 16 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with prediabetes displayed markers of liver function injury, such as elevated ALT and AST levels (35). Among them, decreased AST/ALT can lead to functional impairment of pancreatic b cells, leading to aggravation of IR, forming a vicious circle, and accelerating the progression from prediabetes to type 2 diabetes (13). In a study of 808 Korean adolescents, Lee and Yang et al (15) found that a positive relationship existed between ALT and metabolic syndrome prevalence, while a negative relationship existed between the AST/ALT ratio and metabolic syndrome prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Excess glucose is returned to the liver, where it may hinder gluconeogenesis and encourage lipogenesis when insulin-resistant tissue is unable to increase glucose absorption (42)(43)(44). As a result of the fat buildup and inflammation that follows, the liver's structure is distorted and destroyed, raising ALT levels (13). AST, a vital enzyme for aerobic metabolism, is not only found in the liver but also in other tissues such as the heart, skeletal muscle, kidney, and red blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations